Jakarta’s Paradiplomacy in Strengthening Cybersecurity through the ASEAN Smart City Networks (ASCN) - Masyhari, Ghulam Ali; Al Furqan, Andi Muhammad Raihan (Journal of Paradiplomacy and City Networks, 2025)
The rapid digital transformation in Southeast Asia has prompted many cities to adopt the smart city concept as a strategic effort to improve public service efficiency and the quality of life for citizens. This shift, however, is not without challenges. As digital infrastructures expand, so do vulnerabilities to cybersecurity threats such as data breaches, cyberespionage, and ransomware. These threats are no longer confined to national domains; instead, they are increasingly localized and require responses not only at the national level but also from sub-national actors. This condition reveals an essential argument in the digital era: cities must not merely be policy recipients but must also become proactive agents in global digital governance. Jakarta’s involvement in the ASEAN Smart Cities Network (ASCN) reflects a strategic shift in urban governance, where cities are no longer passive recipients of national policy but active players in regional cybersecuritiy cooperation. ASCN serves not only as a policy forum but also as a diplomatic platform for exchanging best practices, forming technological partnerships, and adopting international standards. This research argues that Jakarta’s participation in ASCN exemplifies strategic paradiplomacy, enabling the city to strengthen its digital security through collaborative projects and knowledge sharing. Using a descriptive qualitative method based on official documents and policy reports, the study discovered that ASCN has facilitated Jakarta’s engagement in regional governance and adoption of global security norms. The findings contribute to the discourse on non-traditional security by depicting that sub-national actors, like Jakarta, could play meaningful roles in cross-border digital governance. It underscores the need to move beyond state-centric perspectives and recognize the growing significance of cities in responding to transnational cyberthreats in Southeast Asia.